2005
DOI: 10.1159/000084587
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure in Diabetes mellitus: Clinical Features and Prognostic Implications

Abstract: We defined the prevalence and impact on survival of clinical bedside variables in 385 patients with symptomatic congestive heart failure (CHF), of whom there were 176 with and 209 without diabetes mellitus. Patients were consecutively hospitalized and admitted for various acute conditions. Following discharge all-cause mortality was recorded. Prevalence and association of various variables with mortality were statistically analyzed. Prevailing in the diabetics versus nondiabetics were younger age (p < 0.05), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies have analyzed hospital glycemic control on the basis of admission [1,4,5] or mean morning [7,8] glucose. However, these may not adequately capture true glycemic exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have analyzed hospital glycemic control on the basis of admission [1,4,5] or mean morning [7,8] glucose. However, these may not adequately capture true glycemic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that diabetes is an independent predictor of mortality in patients with CHF, but little is known about the relative importance of various metrics of glycemic control and CHF outcomes in the hospital [2,3]. Several investigators have shown that admission glucose in patients with CHF is independently associated with mortality [1,4,5], although this finding is not universal [6]. However, admission glucose does not provide a basis for intervention and more comprehensive assessments of glucose exposure may be useful for characterizing any association between mortality and glycemic control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly one-third to one-half of people with HF have concomitant DM (Adams et al, 2005; Greenberg et al, 2007; Masoudi & Inzucchi, 2007; Sarma et al, 2013). There is a 40% to 80% increased risk of mortality among HF patients with DM, and a reported 1.6 fold increase in the relative risk for rehospitalization over those without DM (Bobbio et al, 2003; De Groote et al, 2004; Domanski et al, 2003; Dries, Sweitzer, Drazner, Stevenson, & Gersh, 2001; From et al, 2006; Gorelik et al, 2005). This is due to both worsening HF and higher burden of other co-morbidities, such as ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%